Peningkatan Keterampilan Membaca Pemahaman melalui Model Pembelajaran Kooperatif Tipe STAD pada Murid Kelas V SDN No. 2 Bababulo - Subianto Basri (Celebes Journal of Elementary Education, 2024)
This research aims to improve reading comprehension skills through the Whole Language approach for Class V Students of SDN No. 2 Bababulo, Kec. Pamboang, Kab. Majene. This type of research is classroom action research (Classroom Action Research) which consists of two cycles where each cycle is carried out in 3 meetings. This research procedure includes planning, implementation, action, observation and reflection. The subjects of this research were fifth grade students at SDN No. Elementary School. 2 Bababulo District. Pamboang District Majene, numbering 29 people. The research results showed that only 18 students or 62.07% completed the first cycle individually from 29 students who met the minimum completion criteria (KKM) or were in the low category. Classically it has not been fulfilled because the average value of learning outcomes obtained was 74.14%, whereas in cycle II where out of 29 students there were 25 students or 86.20% had fulfilled the KKM and classically it had been fulfilled, namely the average obtained was 83. 10% or in the high category. Based on the results of the research above, it can be concluded that the reading comprehension skills of Class V students at SDN No. 2 Bababulo District. Pamboang District Majene through STAD Type Cooperatives increased.